Otimização do sequenciamento de atividades de manutenção de aeronaves com abordagens de programação de projetos - Pileggi, Mateus de Oliveira (Universidade Federal de São Carlos, 2019)
The present work analyses the aircraft maintenance activities scheduling that can be seen as a production scheduling problem. The work is developed with the collaboration of a mid-size maintenance center located in Brazil that maintains a fleet of dozens of aircrafts. The case study aims to develop, propose and apply two optimization models that appropriately represents the problem using project scheduling methods. These methods are based in the Resource Constrained Project Scheduling Problems, already explored in other industrial settings. The aim is to contribute to enhance the aircraft maintenance activities scheduling and analyze the efficiency of the proposed models to solve the problem. Computational results obtained from the model application to real instances of the case study are presented and analyzed, showing the potential of this kind of approach to represent and optimize the aircraft maintenance. The results show that both models have the potential for practical application, each one with its objective function characteristics, achieving better results when compared to the case study practice.
Optimizing the sequencing of aircraft maintenance activities using project scheduling approaches
Keywords: Manutenção aeronáutica; Indústria aeronáutica; Aviação; Sequenciamento de atividades; Programação da produção; Programação de projetos; Makespan; Leadtime médio; Aircraft maintenance; Aeronautical industry; Aviation; Activities sequencing; Production scheduling; Project scheduling; Makespan; Average leadtime; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL; 9. Indústria, Inovação e Infraestrutura